Stimuli-responsive microgels for controlled deposition of gold nanoparticles on surfaces. Issue 11 (30th October 2020) - Wei, Menglian; Xu, Wenwen; Gao, Feng; Li, Xue; Carvalho, Wildemar S. P.; Zhang, Xueji; Serpe, Michael J.
Abstract : A variety of gold nanoparticle (AuNP) core/poly( N -isopropylacrylamide) (pNIPAm) shell microgels (Au@pNIPAm) were generated and used to control AuNP deposition on surfaces. Abstract : A variety of gold nanoparticle (AuNP) core/poly( N -isopropylacrylamide) (pNIPAm) shell microgels (Au@pNIPAm) were generated using seed-mediated polymerization. The shell thickness and AuNP core diameter were easily tunable at the time of synthesis. The resultant Au@pNIPAm microgels were characterized via photon-correlation spectroscopy, transmission electron microscopy and ultraviolet-visible spectroscopy. AuNP arrays were generated by "painting" the microgels on a surface, using the shell thickness to define the distance between the AuNPs, followed by shell removal via plasma etching. We found that when the pNIPAm shell thickness decreased ( via its tuning at the time of synthesis or deposition at elevated temperature at which the shell is collapsed) the AuNPs were closer to one another. We also showed that via sequential deposition Au@pNIPAm microgels with different AuNP core sizes could be deposited on a single surface. The presented "painting protocol" offers a facile way to coat large area surfaces quickly which is not easily achievable using other approaches. We envision that this approach is extremely versatile, allowing a number of different nanomaterials embedded in pNIPAm shells to be deposited/patterned on surfaces. With the control over the deposition on the surface that we show here, we hope that the Au@pNIPAm microgels will find use in lithography/surface patterning applications.